Keeratan Hubungan antara Dimensi Sarang Bambu dan Perkembangbiakan Lebah Trigona sp. (Correlation of Bamboo Nest Dimension and Trigona sp. Bee Productivity) - Kapitanhitu, Rusli; Cahyono, Tekat Dwi; Kaliky, Fitriyanti (Kementerian Perindustrian, 2018)
The Trigona sp. bees do not require specific breeding treatment. Nevertheless, selection of shade, container or media to cultivate this stingless bee can be engineered to increase the production of honey. This study was aimed to determine the effect of diameter, length, and thickness of bamboo used as a beehive of Trigona sp. The beehive was prepared from 54 thorny bamboo’s culms with various sizes. Hole was made on the culms where the queen and propolis could be inserted into the culms. Those inserted culms were then put in the cultivation place. The honey resulted from each culm was calculated after 4 months of the cultivation. The results showed that total honey production, HPB (honey, propolis, bee bread), and bee bread were 221.3 g, 792.7 g, and 33.8 g. Regression analysis revealed that there wa a significant effect of bamboo’s diameter on honey production, but not on bee bread, egg’s weight and HPB. Recommended diameter of bamboo culms for the cultivation of Trigona sp. was about 6-12 cm to obtain better quantity of honey